Why is China Growing so Fast? - Khan, Mohsin (IMF Working Papers; Working Paper ;, 1996)
China has been growing at a spectacular rate in recent years, enabling per capita incomes to almost quadruple in only the last decade and a half This paper identifies the sources of economic growth in China from 1953 to 1994. While capital accumulation played an important role in China's economic growth throughout the period, it is basically the sharp and sustained increase in productivity that accounts for the unprecedented economic growth observed during the reform period. The productivity gains largely reflect market-oriented reforms, especially the expansion of the nonstate sector, as well as China's 'open door' policy that brought about a dramatic expansion in foreign trade and foreign direct investment.